2018
DOI: 10.1155/2018/9801258
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness, Grit, School Attendance, and Academic Performance among Adolescents

Abstract: Objective The purpose of this study was to examine the relationship of grit as a construct representing perseverance to overcoming barriers and the total number of school absences to academic performance (AP) while controlling for sociodemographics, fitness (i.e., PACER), and Body Mass Index (BMI). Methods Adolescents (N = 397, SD = 1.85; 80.9% females; 77.1% Hispanic) from an urban, minority-majority city in the Southern United States completed the FitnessGram® assessment of physical fitness (e.g., aerobic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 28 publications
3
36
0
4
Order By: Relevance
“…This study supported the results of previous research indicating that students with higher grit and self-control scores were more likely to demonstrate better academic performance [7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 90%
“…This study supported the results of previous research indicating that students with higher grit and self-control scores were more likely to demonstrate better academic performance [7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 90%
“…Among 54 studies that examined the effect of overall grit on students’ academic achievement, more than half (35 studies) reported significant positive results (Akos & Kretchmar, ; Cosgrove et al, ; Duckworth & Quinn, ; Duckworth et al, ; Dumfart & Neubauer, ; Farroll, ; Hill, ; Huang & Zhu, ; B. C. Lee, ; Lee & Sohn, ; Li et al, ; Lin & Chang, ; Mason, ; Muenks et al, ; Sheehan, ; Strayhorn, ; Tovar‐García, ; Wang et al, ; Williams, ), whereas one study reported a significant negative result (Climer, ). Six studies reported mixed results (Al‐Mutawah & Fateel, ; Cross, ; Kelly et al, ; O'Neal et al, ; Pate et al, ; Rojas, ) and eight studies reported nonsignificant results (Batres, ; Bazelais, Lemay, & Doleck, ; Engel, ; Flanagan & Einarson, ; Palisoc et al, ; Saunders‐Scott et al, ; Smith, ; Zurlo, ).…”
Section: Resultsmentioning
confidence: 99%
“…Grit's predictive role has been corroborated in educational, psychological and social constructs, such as mental health (Kleiman, Adams, Kashdan, & Riskind, ), student learning motivation (Myers, Wang, Black, Bugescu, & Hoeft, ), and success in school and the workplace (Eskreis‐Winkler, Shulman, Beal, & Duckworth, ). Within academic settings, empirical studies have repeatedly shown that grit plays a significant role in individual academic success (Akos & Kretchmar, ; Cosgrove, Chen, & Castelli, ; Duckworth & Quinn, ; Hodge, Wright, & Bennett, ), some failed to detect an association between grit and academic achievement (Al‐Mutawah & Fateel, ; Cross, ; Rojas, ). As the data do not converge, these findings may result in a vague relationship between grit and academic achievement, which warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BioMed Research International Physical fitness was a commonly admitted key factor to people's physical and mental health, and it was found to be strongly relevant to the academic performance of children and adolescents [31][32][33][34]. Also, researchers did a few studies on the impact of physical fitness on college students.…”
mentioning
confidence: 99%